Social Media Portraits and YouTubers during the COVID-19 Pandemic in Indonesia - Supadiyanto, Supadiyanto; Murti, Sudaru (Technium Education and Humanities, 2022)
Social media and Internet technology are like a coin. The existence of social media and Internet technology is a prospective medium for the realization of digital media. The advantages of digital media are that it has a high level of interactivity, high interconnectivity can be broadcast live or delayed, stored eternally; easy to use and inexpensive tends to be free. The fantastic growth of internet and social media users at this time has made the existence of these mediums shift and threaten conventional media technology (newspapers, radio, and analog television), and even threaten the existence of digital TV and radio broadcasting stations. Research problem formulation: how is the constellation map of social media and YouTubers during the COVID-19 pandemic in Indonesia? How is the competition between YouTubers in Indonesia during the COVID-19 pandemic in attracting social media users and Internet users in the world? The research paradigm is quantitative and qualitative. Data collection techniques were carried out by questionnaires, literature review, documentation, and interviews. As a result, the use of social media and the internet has experienced an extraordinary spike at the national and world levels. The collapse of several media companies during the COVI-19 pandemic was a major blow to the media industry. Media workers and media entrepreneurs are obliged to carry out digital transformation, by optimizing Internet and social media technology. The public must also be smarter in using internet technology and social media as a productive medium, not just as a consumptive and entertainment medium. Considering the various professions and jobs using internet technology and social media, nowadays and in the future it is very prospective.